El rey de los tejones - Hensher, Philip (Libros del Asteroide, 2013)
Hanmouth, situated where the Hand River flows into the Bristol Channel, is usually quiet and undisturbed. But it becomes the center of national attention when an eight-year-old girl vanishes. This tragic event serves to expose the range of segregated existences in the town, as spectrums of class, wealth, and lifestyle are blurred in the investigation. Behind Hanmouth's closed doors and pastoral façade, the extraordinary individual lives of the community are laid bare.